2006
DOI: 10.1192/bjp.189.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Insight in psychosis and neuropsychological function

Abstract: Neuropsychological dysfunction, specifically impairment of set-shifting and error monitoring, contributes to poor insight in psychosis. Specific relations with different dimensions of insight and the putative role of metacognitive functions require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
155
6
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(193 citation statements)
references
References 60 publications
(34 reference statements)
21
155
6
11
Order By: Relevance
“…Consistent with an earlier meta-analysis 131 and systematic review 13 , a more recent meta-analysis has found a very weak link between neurocognition and insight 132 . Other published studies continue to fail to find a link between insight and multiple facets of neurocognition in patients in varying phases of illness 47,51,133,134 .…”
Section: World Psychiatry 17:1 -February 2018supporting
confidence: 62%
“…Consistent with an earlier meta-analysis 131 and systematic review 13 , a more recent meta-analysis has found a very weak link between neurocognition and insight 132 . Other published studies continue to fail to find a link between insight and multiple facets of neurocognition in patients in varying phases of illness 47,51,133,134 .…”
Section: World Psychiatry 17:1 -February 2018supporting
confidence: 62%
“…All findings were in the anticipated direction, with lower awareness being associated with poorer WCST performance. The most comprehensive and quantitative systematic review and meta-analysis of work in this area [49] suggests that WCST performance has more in common with awareness than other measures, such as IQ or memory, with 13 studies creating a pooled effect size of r ¼ 0.23. The pattern of neuropsychological impairment associated with poor insight in first-episode psychosis (FEP) is also unclear.…”
Section: Clinical Insightmentioning
confidence: 99%
“…Nous avons donc opté pour une troisième approche, intermédiaire, qui consiste à remplacer la valeur manquante par la limite inférieure de l'intervalle de confiance de la taille de l'effet composé. Il s'agit d'une approche dont la validité est reconnue (Aleman et al, 2006).…”
Section: Analyses Statistiquesunclassified